Psychometric properties of the Mastery Scale-Chinese version: Applying classical test theory and Rasch analysis. (November 2013) - Chen, Yun-Ling; Hsiung, Ping-Chuan; Chung, Lyinn; Chen, Shing-Chia; Pan, Ay-Woan
Abstract: Aims: This study examines the reliability and validity of the Mastery Scale-Chinese version (MS-C) when applied to three groups diagnosed with major depression, schizophrenia, or HIV/AIDS. Methods: The individuals participating in the study were recruited from outpatient units of a medical center and a municipal hospital in northern Taiwan. The study sample ( n = 2009) included 237 patients with depressive disorders, 160 with schizophrenia, and 1612 with HIV/AIDS. The reliability and construct validity of the MS-C was evaluated by confirmatory factor analysis (CFA) and Rasch analysis. Results: The results of the CFA showed that the MS-C has adequate construct validity with all indices meeting the criteria, except for chi-square values. The Rasch analysis supported the four-point rating scale structure and a unidimensional construct of the MS-C. The DIF analysis showed that all items demonstrated stable measurement properties among the different diagnosis groups (major depression, schizophrenia, HIV/AIDS). Conclusion: This study found that MS-C has acceptable psychometric qualities in terms of reliability, construct validity, rating scale performance, and item characteristics when applied to patients with depression, schizophrenia, and HIV/AIDS in Taiwan.